2005
DOI: 10.1007/s10494-005-2943-y
|View full text |Cite
|
Sign up to set email alerts
|

Heat Fluxes and Airflow Patterns Through Roof Windows in a Naturally Ventilated Enclosure

Abstract: Experiments were carried out to study the airflow and heat transfer through continuous vertical roof openings of a naturally ventilated greenhouse. The major goals of this work were to investigate the effect of ambient wind speed and direction with respect to the greenhouse on the mean and turbulent characteristics of the air velocity and heat transfer through openings with and without insect-proof screens. Air velocity and temperature were measured simultaneously at two edges of the opening using one-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…That is to say, uy and uz components may take a minor contribution to the mass-flow rate and may even be the consequence of rejected flow or formation of small ); outer side of the IPS at the window ( gronomy 2022, 12, x FOR PEER REVIEW 15 of 18 through the porous mesh. For the total airflow velocity u, the results obtained agree with the observations made by Teitel and Tanny [27], which confirms that the turbulence energy decreases and the spectral decay rate is increased. It is obvious that this loss of energy at high frequency is what produces the reduction in the velocity fluctuations of ux (seen in Figure 5).…”
Section: Theoretical Foundations Of Turbulence Characteristicssupporting
confidence: 89%
See 3 more Smart Citations
“…That is to say, uy and uz components may take a minor contribution to the mass-flow rate and may even be the consequence of rejected flow or formation of small ); outer side of the IPS at the window ( gronomy 2022, 12, x FOR PEER REVIEW 15 of 18 through the porous mesh. For the total airflow velocity u, the results obtained agree with the observations made by Teitel and Tanny [27], which confirms that the turbulence energy decreases and the spectral decay rate is increased. It is obvious that this loss of energy at high frequency is what produces the reduction in the velocity fluctuations of ux (seen in Figure 5).…”
Section: Theoretical Foundations Of Turbulence Characteristicssupporting
confidence: 89%
“…However, in the longitudinal component u x , the energy transported in the larger scales (at low frequency) is maintained after passing through the mesh, whereas the energy transported by the smaller scales (high frequency) is dissipated or lost when passing through the porous mesh. For the total airflow velocity u, the results obtained agree with the observations made by Teitel and Tanny [27], which confirms that the turbulence energy decreases and the spectral decay rate is increased. It is obvious that this loss of energy at high frequency is what produces the reduction in the velocity fluctuations of u x (seen in Figure 5).…”
Section: Influence Of the Insect-proof Screen On The Turbulence Of Th...supporting
confidence: 89%
See 2 more Smart Citations
“…Different turbulence models cause differences in speed, temperature and humidity patterns, confirming the importance of choosing the model that most closely matches the actual conditions of turbulence (Roy and Boulard, 2005). Teitel and Tanny (2005) showed that the output of the turbulent heat flux is mainly due to cold air entering the greenhouse, which produces hot and cold eddies that enter and leave the greenhouse. Roy and Boulard (2005) showed the effects of wind direction on climate parameters inside the greenhouse are usually simulated with the use of different turbulence models available, to determine the energy balance between the flow of perspiration and the flow of radiation.…”
Section: Turbulence and Buoyancymentioning
confidence: 93%